IMPACT OF GENDER DISCRIMINATION ON ADOLESCENT GIRLS - 1. Rashmi Yadav , 2. Dr Afiya Bano (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
After independence, no kind of inequality or disparity has been legally recognized in India. Equal opportunities have been provided to all and special opportunities have been provided to socially or culturally backward communities. Half the population i.e. women have the second status in the society, to whom the Indian Constitution has provided equal opportunity and has prohibited any kind of discrimination. But the behavior of a person is governed and controlled by social and cultural values, so inequality on the basis of sex or gender is still common. This is the reason why women are discriminated against everywhere, from home to outside. This type of discrimination has an adverse effect on various areas of their life and their personality development is hampered. Despite many efforts, social, intellectual, physical, economic and various types of discrimination are seen against women. As a result, violence and crime against women and young women continue. In this research article, an attempt has been made to examine the consequences of gender discrimination against adolescent girls on the basis of secondary data.